Mining Halophytes for Plant Growth-Promoting Halotolerant Bacteria to Enhance the Salinity Tolerance of Non-halophytic Crops - Etesami, Hassan; Beattie, Gwyn A. (Frontiers in Microbiology, 2018)
Salinity stress is one of the major abiotic stresses limiting crop production especially in arid and semi-arid regions. It is well known that the application of PGPRs (plant growth promoting rhizobacteria) is a promising strategy to ameliorate the crop production under optimal or non-optimal conditions. Isolation and application of salt-tolerant or halophilic PGPRs will facilitate the development of saline soil-based agriculture. Halophytes are a useful reservoir of halotolerant-bacteria with plant growth-promoting potential. Investigation in functional interactions between plants and microorganisms helping salt stress tolerance is gaining interest. Here, the recent studies conducted on the use of salt-tolerant or halophilic PGPRs stimulating plant growth and increasing the tolerance of non-halophyte crops to salinity were reviewed. This review shows that isolating halophilic PGPRs from the rhizosphere of halophyte species can be an effective avenue (as bio-inoculants) to promote saline soil-based agriculture (non-halophyte crops). Use of halophilic PGPRs is predicted to become a suitable strategy and an emerging trend in sustainable enhancement of non-halophyte crop growth. The great potential of halotolerant PGPRs should be carefully considered to ensure the enhanced need of food production within the framework of a raising world population and continuing climate changes. This review article also highlights future research needs about use of halotolerant PGPRs under salinity stress.